2019
DOI: 10.37358/rc.18.12.6803
|View full text |Cite
|
Sign up to set email alerts
|

Controled Ovarian Stimulation with Urinary Gonadotrophins and Recombinant Gonadotrophins in Current Practice

Abstract: The main objective of the this study is to compare the effectiveness of ovarian stimulation with recombinant gonadotrophins (FSHr) versus urinary gonadotrophins (hMG) within the number of oocytes obtained and the number of embryos in the two patient groups, according to age groups and associated pathologies. The study design was retrospective, monocentric. All patients (71) who have addressed the In Vitro Fertilization Clinic of the Prof. Dr. Panait Sirbu Clinical Obstetrics and Gynecology Hospital during 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…An adequate vitamin D level during pregnancy ensures an optimum vitamin D level to the fetus, resulting in a normal bone development due to the fact that vitamin D crosses the placenta and creates deposits especially during the 3 rd trimester. A vitamin D deficit in women during pregnancy is most prevalent in high risk populations [9]. Low levels of vitamin D in pregnancy seems to be associated with an increased risk for gestational diabetes mellitus, preeclampsia and fetal growth restriction and in the long term, for deficient skeletal homeostasis, congenital rickets, early bone fractures and immune deficiencies [10][11][12].…”
Section: Biochemical Mechanismsmentioning
confidence: 99%
“…An adequate vitamin D level during pregnancy ensures an optimum vitamin D level to the fetus, resulting in a normal bone development due to the fact that vitamin D crosses the placenta and creates deposits especially during the 3 rd trimester. A vitamin D deficit in women during pregnancy is most prevalent in high risk populations [9]. Low levels of vitamin D in pregnancy seems to be associated with an increased risk for gestational diabetes mellitus, preeclampsia and fetal growth restriction and in the long term, for deficient skeletal homeostasis, congenital rickets, early bone fractures and immune deficiencies [10][11][12].…”
Section: Biochemical Mechanismsmentioning
confidence: 99%
“…Bisphenol A (BPA) is another phenol associated with precocious puberty in girls, which is often used to make household products [4,19]. Animal studies have demonstrated estrogenic properties for BPA, this compound being associated with earlier onset of puberty in female rats, leading to a precocious vaginal opening [12,20,21].…”
Section: Phenolsmentioning
confidence: 99%
“…GnRH leads to a rise in pulsatile secretion of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) from the anterior pituitary gland. Gonadotropin release is a trigger for the gonads, the final result being the onset of ovulatory menstrual cycles [1,3,4].…”
mentioning
confidence: 99%